In Vivo Activation of AMP-Activated Protein Kinase Attenuates Diabetes-Enhanced Degradation of GTP Cyclohydrolase I - Shuangxi Wang; Jian Xu; Ping Song; Benoı̂t Viollet; Ming‐Hui Zou (2009)
OBJECTIVE The activation of AMP-activated protein kinase (AMPK) has been reported to improve endothelial function. However, the targets of AMPK in endothelial cells remain poorly defined. The aim of this study was to test whether AMPK suppresses the degradation of GTP-cyclohydrolase (GTPCH I), a key event in vascular endothelial dysfunction in diabetes. RESEARCH DESIGN AND METHODS Both human umbilical vein endothelial cells and aortas isolated from streptozotocin-injected diabetic mice were assayed for phospho-AMPK (Thr172), GTPCH I, tetrahydrobiopterin (BH4), and endothelial functions. RESULTS Oral administration of metformin (300 mg · kg−1 · day−1, 4 weeks) in streptozotocin-injected mice significantly blunted the diabetes-induced reduction of AMPK phosphorylation at Thr172. Metformin treatment also normalized acetylcholine-induced endothelial relaxation and increased the levels of GTPCH I and BH4. The administration of AICAR, an AMPK activator, or adenoviral overexpression of a constitutively active mutant of AMPK abolished the high-glucose–induced (30 mmol/l) reduction of GTPCH I, biopeterins, and BH4 but had no effect on GTPCH I mRNA. Furthermore, AICAR or overexpression of AMPK inhibited the high-glucose–enhanced 26S proteasome activity. Consistently, inhibition of the proteasome by MG132 abolished high-glucose–induced reduction of GTPCH I in human umbilical vein endothelial cells. Further, aortas isolated from AMPKα2−/− mice, which exhibited elevated 26S proteasome activity, had reduced levels of GTPCH I and BH4. Finally, either administration of MG132 or supplementation of l-sepiapterin normalized the impaired endothelium-dependent relaxation in aortas isolated from AMPKα2−/− mice. CONCLUSIONS We conclude that AMPK activation normalizes vascular endothelial function by suppressing 26S proteasome-mediated GTPCH I degradation in diabetes.